2013
DOI: 10.9790/0661-155107112
|View full text |Cite
|
Sign up to set email alerts
|

Intrusion Detection System Based on K-Star Classifier and Feature Set Reduction

Abstract: Network security and Intrusion Detection Systems (IDS's) is an important

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Moreover, it was observed that the Lazy classifier yielded superior results compared to other technique. Mahmood and Hussein [15] employed the K-star algorithm in conjunction with filtering analysis to construct a network intrusion detection system. They conducted experimental analysis using the K-star dataset, a modified version of the intrusion detection benchmark dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Moreover, it was observed that the Lazy classifier yielded superior results compared to other technique. Mahmood and Hussein [15] employed the K-star algorithm in conjunction with filtering analysis to construct a network intrusion detection system. They conducted experimental analysis using the K-star dataset, a modified version of the intrusion detection benchmark dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Both KNN and K* are instancebased learners, which means that the class of a test instance is decided by the class of training instances that are like it, as defined by some similarity function. In the case of K*, an entropy-based distance function is deployed as a similarity function while KNN is based on the Euclidean distance function [42,43]. Table 2 shows the parameters of KNN and K* as deployed in this study.…”
Section: Algorithms Parameter Settingmentioning
confidence: 99%